2017
DOI: 10.18203/2320-6012.ijrms20170656
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and risk factors among young patients presenting with stroke in a tertiary care hospital in South India

Abstract: Background: Stroke is one of the leading causes of disease and death throughout the world with the incidence rising steeply with age. The occurrence of stroke in young is rare but once it occurs the outcome is severe. Limited studies have been performed in the Indian population to describe the clinical presentation and etiology of young adults with stroke. The objective of present study is to assess the etiology, risk factors and clinical presentation among patients who visit a tertiary care centre with a clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Research indicated that dyslipidemia in individuals with ischemic stroke was around 15.6% [ 8 ], whereas a local investigation found it at 37.1% [ 9 ]. Subburaj et al have shown a much more significant percentage (65.7%) of dyslipidemia in ischemic stroke patients [ 10 ]. In Pakistan, dyslipidemia is a very under-reported cause of stroke due to a lack of central registry and limited resources in the third world, requiring laboratory investigations to diagnose dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Research indicated that dyslipidemia in individuals with ischemic stroke was around 15.6% [ 8 ], whereas a local investigation found it at 37.1% [ 9 ]. Subburaj et al have shown a much more significant percentage (65.7%) of dyslipidemia in ischemic stroke patients [ 10 ]. In Pakistan, dyslipidemia is a very under-reported cause of stroke due to a lack of central registry and limited resources in the third world, requiring laboratory investigations to diagnose dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…According to research, dyslipidemia was present in about 15.6% of people who had ischemic strokes 15 ; however, a local examination discovered - ----------------------------------------------------------------------------------------Received on 10-08-2022 Accepted on 18-01-2023 that it was 37.1% 16 . Patients who had ischemic strokes had a substantially higher rate of dyslipidemia (65.7%), according to Subburaj et al 17 Due to a lack of a central registry and the restricted resources in the third world, dyslipidemia is a severely under-reported cause of stroke in Pakistan, necessitating laboratory tests to detect the condition.…”
Section: Introductionmentioning
confidence: 99%